Territorial governance and social innovation in regional development processes in mining territories: a theoretic model under construction - Gentil,Paula Pessoa de Castro (2019)
Abstract There are serious contradictions between the proclaimed economic benefits obtained by localities where the mineral extraction industry historically operates, and the results recorded in research work. Studies have pointed out serious problems and negative consequences from the mineral extraction industry’s questionable form of management and relationship with the local environment. These practices have increased the socioeconomic and environmental vulnerability of the territories, both in local and regional dimensions. Studies about development indicate the existence of a positive relationship between governance and economic growth, and between innovation and economic growth. There are also studies that point out innovative processes as essential to local and regional development because they prioritize the territorial diversity and develop opportunities focused on the profile of each region. However, this discussion is still restricted to the economic and exclusive point of view of the industrial sector, which limits the analysis from the perspective of regional development. To unravel the nature of the still unclear relationship between territorial governance and social innovation and the effects of this relationship in regional development processes in mining territories, this article raises a set of six theoretical propositions, which forms a schematic model for further empirical investigation. The aim is to use this model to search for similarities and peculiarities, and to establish parallel or comparative analysis between diverse and different case studies.